The 3D leader take your leadership to the next dimension - Mauri, Terence (Ascent Audio, 2023)
The 3D Leader will provide you with a practical set of actions to lead faster, smarter, and better in a VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) world, whatever the size or type of organization. Use the Bold, Brave, and Beyond mindsets in three easy and practical steps to help you lead faster, smarter, and better by a factor of 10, not 10 percent. Much of what leaders know is no longer enough, and most organizations are still trapped in outdated twentieth century mindsets that focus too heavily on efficiency and protecting the past, rather than inventing the future. Drawing on extensive research, this book reveals the three winning mindsets repeated by respected leaders again and again, which will take your leadership skills to the next level: 1. BOLD: Build a 10x mindset where you can take bold leaps into the future. 2. BRAVE: Build a challenge culture where it's safe to speak up and bring your best self to work. 3. BEYOND: Navigate the rapid pace of change, unlock your leadership purpose, and be the change. The 3D Leader will equip you with a practical set of actions for you to completely reimagine how you lead. After listening to the book, you will have the know-how and tools to lead faster, smarter, and better.